2008
DOI: 10.4103/1319-3767.39619
|View full text |Cite
|
Sign up to set email alerts
|

Sustained virologic response to peginterferon α-2a and ribavirin in 335 patients with chronic hepatitis C: A tertiary care center experience

Abstract: Background/Aim:This retrospective study assessed the efficacy, safety, and the predictors of sustained viral response (SVR) to a 48-week-course of peginterferon α-2a (Pegasys) and ribavirin combination therapy in 335 consecutive Saudi patients with chronic hepatitis C virus (HCV) infection.Materials and Methods:Clinical, biochemical, and virological parameters were collected at time 0 (pretreatment) and at 12, 24, 48, and 72 weeks posttreatment. The mean ± SD age was 49.1 ± 13.0 years; 229 (68.4%) were males, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…This is comparable with response rate (63%) predicted by Al Ashgar et al, 19 but is higher compared to that reported by kamal et al, 20 which was 48 %. And is lower compared to that reported by Al Ashgar et al, 21 which was (75.6%).…”
Section: Discussioncontrasting
confidence: 62%
“…This is comparable with response rate (63%) predicted by Al Ashgar et al, 19 but is higher compared to that reported by kamal et al, 20 which was 48 %. And is lower compared to that reported by Al Ashgar et al, 21 which was (75.6%).…”
Section: Discussioncontrasting
confidence: 62%
“…This needs to be confirmed in another prospective trial. We have recently published a study involving 335 patients with HCV infection of all genotypes 61. It showed that the response of genotype 4 patients to combination therapy is more or less similar to genotype 1.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible explanations for this relatively low SVR is the use of an 800 mg fixed dose of ribavirin daily. More recently Al Ashgar et al [8] published their results in which 335 patients treated with PEG-IFN a-2a and ribavirin achieved an SVR rate of around 48%. In this study, they adjusted the ribavirin dose according to the body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The data on treating hepatitis in the Middle East, in which genotype 4 predominates, is limited. A recent study assessing sustained virological response (SVR) in Saudi Arabia revealed an SVR rate of around 48% in patients infected with HCV genotype 4; however, only PEG-IFN a-2a (PEGASYS) was used and they also included patients who were considered difficult to treat [8] . Limitations of other studies include small number of patients, use of conventional interferons, and the lack of viral genotype data [9] .…”
Section: Introductionmentioning
confidence: 99%